Effects of wellbore stability to sand production - Samsuri, Ariffin; Subbiah, Surej Kumar (1998)
The paper describe a series of laboratory experiment to observe the effects wellbore stability to sand production. The wellbore stability is the most important of aspect that should be considered during and production activities. The paper will presented only the effect of wellbore stability due the structure design at production zone i.e. perforated cased wellbore. The physical model has been design as wellbore where different borehole angle and perforation parameter (shot density and perforation pattern) has been impose to see the effect on the stability and sand production. Generally all models fail and sand particles were produced and found that stable perforated wellbore produce less sand particles.